Inner filter effect on fluorescence dyes spectra in methanol solution - Sukprasong S. (2017)
© 2016 Trans Tech Publications, Switzerland. This research was conducted to study the inner filter effect on the fluorescence spectra of fluorescence dyes. The concentration effect on all of fluorescent dye solutions showed the same trend in terms of changes in fluorescence intensity spectra. At low concentrations, the fluorescence intensity increased when the concentration of fluorescent dye solution increased. However, at high concentrations, the fluorescence intensity decreased when the concentration of fluorescent dye solution increased. Interestingly, the result of fluorescence spectra in dye solutions showed that the fluorescence intensity maxima in all dye solutions were shifted to a higher wavelength (red-shift) when the concentration of fluorescent dye solution increased. The results of concentration effect on fluorescence intensity and wavelength-shift in dyes solution can be explained by inner filter effect on fluorescent dye solutions.